MUHAMMADIYAH YOUTH'S PROCLAMATION OF ISLAMIC CIVILIZATION IN INDONESIA THROUGH DAKWAH COMMUNICATION - Candra Darmawan; Kamaruddin Kamaruddin; Toha Rudin (Khazanah: Jurnal Studi Islam dan Humaniora, 2023)
This article delves into the pivotal role of Muhammadiyah Youth's preaching communication in Indonesia, focusing on its contribution to the nation's independence. The organization's primary aim is to address and rectify deviations within the da'wah process, while also promoting an advanced and educated social and educational structure. Employing a qualitative research methodology through library research, the study draws from primary sources, including Books of Islamic Intellectual Treasures, Islamic Intellectual Reform, Contextualization of Islamic Doctrine in History, and Intellectual Tradition of Malay Scholars of the 18th Century AD, alongside relevant secondary data. Data collection involves four techniques: heuristics, verification, interpretation (analysis and synthesis), and historiography. The research reveals that Muhammadiyah Youth's da'wah communication encompasses three key domains: godliness, focusing on God, His attributes, and the universe's relationship with Him; morality, addressing human behavior, relationships with God, others, and the universe; and physics, exploring nature's growth and development.The relevance of Muhammadiyah Youth's preaching communication is demonstrated through four doctrines: enlightening the people, promoting charitable actions, fostering cooperation for virtue, and steering clear of political pragmatism. To ensure continuous and responsive da'wah in a dynamically changing society, it is crucial to anticipate the negative implications of information and communication globalization. The study advocates for informative, comprehensive, targeted, and sustainable preaching, leading to the effective implementation of Islamic sharia in society, transcending mere legal aspects.